Developing Indonesian Language Teaching Materials Based on the Mime Model: A Lesson from It’s Validity, Practicality, and Effectiveness. - Hadi Wardoyo; Riswanda Himawan; Heny Subandiyah; Suryantoro Suryantoro (JOLLT Journal of Languages and Language Teaching, 2026)
The growing demand for advanced literacy skills requires reading instruction at the junior high school level to move beyond surface comprehension toward integrative, analytical, and reflective reading practices. However, Indonesian language instruction remains largely dependent on conventional teaching materials that do not systematically integrate extensive and intensive reading strategies. This study aimed to develop Indonesian language teaching materials based on the Integrative Extensive–Intensive Reading (MIME) model to enhance students’ reading comprehension and text analysis skills. This research employed a R&D approach. Data were collected through classroom observations, interviews, document analysis, expert validation sheets, student response questionnaires, and reading comprehension tests. The study involved Indonesian language teachers and students at Malang, East Java, with 30 students participating in the limited field trial. The developed materials were evaluated by subject matter experts, instructional design experts, and graphic design experts before being implemented in an experimental class and compared with a control class to examine their effectiveness. The validation results indicated that the developed teaching materials achieved a very high level of validity. Effectiveness testing revealed a statistically significant difference between the experimental and control groups (p = 0.003 < 0.05). These findings demonstrate that the MIME-based teaching materials are valid, practical, and effective in improving students’ reading comprehension, text analysis skills, and learning engagement. Practically, the developed teaching materials can serve as an alternative instructional resource for Indonesian language teachers to implement integrative reading instruction and strengthen students’ higher-order literacy skills at the junior high school level.